Biosafety measures in dental practice: Literature Review - Barbieri, Ana Amélia; Feitosa, Fernanda; Ramos, Carolina Judica; Teixeira, Symone Cristina (Brazilian Dental Science, 2019)
Objective: There is a great concern with biosafety nowadays, given the knowledge of diseases and potential complications in health practice. In this context, this review aims to provide information capable of improving good health practices and consequent minimization of operational risks in dental practice. Material and Methods: A review of biosafety literature was carried out covering the last seven years considering the health descriptors: "odontologia" and "biossegurança" / "Contenção de Riscos Biológicos" in the following Databases: Biblioteca Virtual em Saúde - BVS (Virtual Health Library); Bibliografia Brasileira de Odontologia - BBO (- Brazilian Bibliography of Dentistry ) and Literatura Latino-Americana e do Caribe em Ciências da Saúde – LILACS (Latin American and Caribbean Literature in Health Sciences); and with the descriptors "dentistry" and "biosecurity" / "Containment of Biohazards" in the Databases: Scientific Electronic Library Online (SciELO), National Library of Medicine (MEDLINE), US National Library of Medicine National Institutes of Health Search (PubMed) and SCOPUS. Results: There were found 33 articles that met the criteria established for this research. Conclusion: From the literature, it is concluded that the evaluation of procedures, knowledge and constant study, the improvement of procedures and joint action of all staff is of fundamental importance so that health improvement can go beyond health care and the resolution of a specific problem. Keywords Dentistry; Containment of biohazards; Biosafety.